2023
DOI: 10.1097/md.0000000000033062
|View full text |Cite
|
Sign up to set email alerts
|

Impact of MAFLD on the complications after hepatectomy in patients with HBV-related hepatocellular carcinoma

Abstract: Metabolic dysfunction-associated fatty liver disease (MAFLD) is a term that was proposed in 2020 by a group of international experts. However, the impact of MAFLD on complications after hepatectomy in patients with hepatocellular carcinoma is not clear. The aim of this study is to explore the influence of MAFLD on the complications after hepatectomy in patients with hepatitis B virus-related hepatocellular carcinoma (HBV-HCC). Patients with HBV-HCC who underwent hepatectomy between January 2019 and December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 34 publications
0
2
0
1
Order By: Relevance
“…Після резекцій 65-70 % і більше паренхіми печінки її функції можуть відновлюватися за рахунок збільшення об'єму шляхом регенерації [2]. Проте, одним із післяопераційних ускладнень гепатектомії є малий розмір й функціонально нездатний печінковий залишок [3]. Тому, для стимуляції проліферативних і репаративних процесів у печінковому залишку може бути ефективне застосування аутомезоконцентрату тромбоцитів (АМК) [4].…”
Section: вступunclassified
“…Після резекцій 65-70 % і більше паренхіми печінки її функції можуть відновлюватися за рахунок збільшення об'єму шляхом регенерації [2]. Проте, одним із післяопераційних ускладнень гепатектомії є малий розмір й функціонально нездатний печінковий залишок [3]. Тому, для стимуляції проліферативних і репаративних процесів у печінковому залишку може бути ефективне застосування аутомезоконцентрату тромбоцитів (АМК) [4].…”
Section: вступunclassified
“…An Italian Liver Cancer Center study showed that out of 6882 patients diagnosed with HCC, 4706 (68.4%) patients were found to have MAFLD [13]. A Chinese study showed that among 514 HBV-HCC patients who underwent radical resection, MAFLD was detected in 117 (22.8%) patients [14]. MAFLD serves as a significant risk factor for the development of HCC and warrants careful consideration from clinicians regarding its potential impact on post-hepatectomy complications.…”
Section: Introductionmentioning
confidence: 99%
“…An Italian Liver Cancer Center study showed that out of 6882 patients diagnosed with HCC, 4706 (68.4%) patients were found to have MAFLD [13]. A Chinese study showed that among 514 HBV-HCC patients who underwent radical resection, MAFLD was detected in 117 (22.8%) patients [14]. MAFLD serves as a signi cant risk factor for the development of HCC and warrants careful consideration from clinicians regarding its potential impact on posthepatectomy complications.…”
Section: Introductionmentioning
confidence: 99%